Yolk color and fatty acids of creole turkey and duck eggs - Hernández-Guzmán, Filogonio Jesús; Rodríguez-Ortega, Alejandro; Ronquillo de Jesús, Elba; Mendoza-Pedroza, Sergio Iban; Aguilar-Méndez, Miguel Ángel; Rodríguez-Ortega, Leodan Tadeo (Ecosistemas y Recursos Agropecuarios, 2025)
Turkey and duck eggs play an important role in backyard poultry farming, because they are a source of animal protein for low-income families in Mexico. The objective of this research was to describe the physical characteristics, yolk color and fatty acid content of duck and creole turkey eggs. Duck eggs (n = 114) and creole turkey (n = 114) eggs were collected from backyard units developed in Valle del Mezquital Hidalgo, Mexico. The variables evaluated were weight, egg width and length, relative weight of yolk, white and shell, yolk color and the fatty acid profile was determined for both types of eggs. The turkey egg had greater (P < 0.05) weight, length and width than the duck egg. The duck egg had a lower (P < 0.05) relative weight of the egg white and a similar (P > 0.05) relative weight of the shell compared to the turkey egg. The yolk color of the turkey egg was higher (P < 0.05) than that of the duck egg. The turkey egg had a slightly higher content of docosahexaenoic acid (DHA). In conclusion, the creole turkey egg was larger than the duck egg. The yolk in the creole turkey egg was more colorful than in the duck egg. The fatty acids present in both types of eggs are beneficial to human health.